The content validity of the Behavioural Appraisal Scales in people with profound intellectual and multiple disabilities: A Delphi study. Issue 1 (14th January 2022) - Wessels, Marleen D.; Paap, Muirne C. S.; van der Putten, Annette A. J.
Abstract: The Behavioural Appraisal Scales (BAS) were developed in The Netherlands to assess functional abilities of people with profound intellectual and multiple disabilities (PIMD). It is recommended that further studies examine the psychometric properties of the BAS. The aim of this study was to evaluate and, if necessary, improve the content validity of the BAS. A two‐round Delphi study was used. In Round 1, parents, researchers and practice professionals indicated for each item whether they would retain, adapt or remove it, explaining their answers. The BAS were adapted based on this feedback. In Round 2, participants were given the adapted version and asked to indicate for each item whether they wanted to retain or remove it, again providing an explanation. Feedback was analysed by calculating the percentage of participants who wanted to retain, adapt or remove a certain item. Content analysis was used to analyse participants' explanations. In Round 1, more than 20% of the participants wanted to remove 11 from the 122 items, and wanted to retain or adapt the remaining items. Seven categories of adaptations emerged: (1) feasibility, (2) the construct the item measures, (3) applicability, (4) similarity among items, (5) splitting items, (6) reassignment and (7) the professionals who score the items. In Round 2, for all items >80% of the participants indicated they wanted to retain the item. Experts felt that the content validity of the BAS could be improved. After the adaptations, the content validity was evaluated as good. Further studies are needed to evaluate whether the new or adapted items are not too easy or too difficult, whether information from different informant groups results in being scored differently, and to evaluate possible differential item functioning.